2020
DOI: 10.1521/pedi_2019_33_408
|View full text |Cite
|
Sign up to set email alerts
|

Disorganized Attachment Interactions Among Young Adults With Borderline Personality Disorder, Other Diagnoses, and No Diagnosis

Abstract: Theorists have suggested that attachment disorganization contributes to the development of borderline personality disorder (BPD). However, few studies have directly observed attachment-related interactions with parents. This study used a newly developed attachment-based coding system to examine whether individuals with BPD were more likely to exhibit disorganized interactions with their mothers than those with (a) other diagnoses (anxiety, depressive, or substance use diagnoses) or (b) no diagnosis. Results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
4
14
0
Order By: Relevance
“…Individuals at risk for borderline personality pattern scored significantly higher on the ADA total score than individuals who are not at risk for borderline personality pattern. This finding is consistent with theoretical explanations (15)(16)(17)60,61) and limited empirical research findings in the literature (14,62). From this point of view, it can be concluded that ADA can significantly distinguish individuals who are at risk for borderline personality pattern from individuals who are not at risk.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Individuals at risk for borderline personality pattern scored significantly higher on the ADA total score than individuals who are not at risk for borderline personality pattern. This finding is consistent with theoretical explanations (15)(16)(17)60,61) and limited empirical research findings in the literature (14,62). From this point of view, it can be concluded that ADA can significantly distinguish individuals who are at risk for borderline personality pattern from individuals who are not at risk.…”
Section: Discussionsupporting
confidence: 90%
“…Examination of the clinical results of adult disorganized attachment has revealed that borderline personality disorder may be particularly important. For instance, adults with borderline personality disorder have been more likely to be classified as disorganized rather than insecure-organized when compared with study participants with other diagnoses (anxiety or depressive disorder) or undiagnosed participants (14). This finding supports the theoretical knowledge that the origin of borderline personality disorder may be based on a disorganized attachment pattern developed in childhood (15,16) and that patients with borderline personality disorder have a disorganized attachment style (17).…”
Section: Introductionsupporting
confidence: 62%
“…Fear-evoking and abusive parental behaviours seem to play an important role in the formation of disorganised attachment and a positive association has been shown between disorganised attachment style and personality disorders as well as other psychopathologies in adulthood (e.g. borderline personality disorder, bad stress management and dissociative behaviours) (Van Ijzendoorn et al ., 1999; Khoury et al ., 2019).…”
mentioning
confidence: 99%
“…In fact, we know that the interpersonal functioning of people with disorganized attachment is characterized by a marked reduction of emotional regulation that leads the person to react with defensive behaviors even in situations of emotionally neutral interpersonal exchanges [38][39][40] . Figure 2.…”
Section: Discussionmentioning
confidence: 99%